Two-Stage capacitated vehicle routing problem for transportation of cherry tomatoes: A case study of Mae Chui community enterprise - Lekhavat, Saowanit; Sanium, Soonthareeya (Agriculture and Natural Resources, 2024)
Importance of the work: Routing is one of the important problems for agricultural section. A community enterprise is a center to pick up the products (cherry tomatoes) from farms and transport them to retailers. Objectives: The aim of this research is to propose two heuristics algorithms to minimize transportation cost and suggest practical route. Materials and Methods: K-mean of machine learning method is applied to clustered the number of tomatoes farm by using Weka software. Mixed Integer Linear Programming combined with proposed heuristics algorithms are applied to solve the problem by using OpenSolver added-in Microsoft Excel. Transportation of cherry tomatoes of Mae Chui community enterprise is used as a case study. Results: K-mean method is applied to cluster the cherry tomatoes farm into the group. For case 1 to case 5, they are clustered into 5 groups while case 6 and case 7 are divided into 13 groups. Experimental results are conducted for various scenarios; productivity, number of trucks and farther regions. The result shows that the proposed heuristic algorithm provides 0.44 to 2.42 percent reduction of the total distance and 0.60 to 2.58 percent reduction of the fuel cost in the 1st stage of transportation. Practical implication is suggested for this study. Main finding: The proposed heuristic algorithms overcome the existing method. This finding can contribute to the operations research fields. Moreover, the practical route is recommended for transportation of cherry tomatoes in a case of Mae Chui community enterprise.